KEBIJAKAN INDONESIA DALAM MENANGANI KASUS FINANCIAL AND TECHNOLOGY (FINTECH) ILEGAL TIONGKOK DI INDONESIA - Ovia Ningsih; Pazli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
International relations continue to grow with the existence of technology that can provide easy information and communication using the internet so that it inspires the business world in financial transaction activities. One way to provide easy information and communication in international political economy activities is with the policies carried out by the Indonesian government in dealing with illegal Chinese Financial and Technology (Fintech) cases in Indonesia. This descriptive research uses library data obtained from primary legal materials such as laws, POJK, PBI and secondary legal materials such as books, journals, theses, articles and websites. This research technique uses library research and document analysis. The research uses a theoretical framework, namely the Neo-Liberalism Perspective, Level of Analysis and Securitization Theory. This research shows that there are illegal Chinese Fintech cases circulating in Indonesia. The Indonesian government provides law enforcement (legal structure), public legal awareness (legal culture) and facilities in the process of law enforcement in the field of information technology. Meanwhile, OJK provides information to the public to remain cautious of peer-to-peer lending fintech companies that are not registered/licensed at OJK. The public is advised not to transact, either as a borrower or as a lender. Keywords : Tiongkok Illegal Fintech, Indonesian Government Policy, POJK